2021
DOI: 10.3390/pr9010131
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Grape Seed Flour on the Antioxidant Profile, Textural and Sensory Properties of Waffles

Abstract: The study aimed to enrich waffle products with grape seed flour, but without affecting their sensory properties. The grape seed flour was obtained from grape pomace, and as an ingredient rich in bioactive compounds such as fiber, polyphenols and minerals, it was used to fortify waffles in concentrations of 1, 3, 5 and 10%. The results for the total polyphenolic content, ferric ion reducing antioxidant power (FRAP) and 2,2-diphenyl-1-picryl-hydrazyl (DPPH) inhibition, showed the highest effect with 10% grape se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 22 publications
3
22
2
Order By: Relevance
“…The results show that the enrichment of the products with grape seed flour significantly ( p < 0.05) affected the amount of polyphenols in the final product. This finding is in accordance with the study examining the effect of adding grape seed flour to waffles [ 20 ]. The increased amount of polyphenols in sample 11 z is also due to the addition of millet flour, made by grinding millet.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The results show that the enrichment of the products with grape seed flour significantly ( p < 0.05) affected the amount of polyphenols in the final product. This finding is in accordance with the study examining the effect of adding grape seed flour to waffles [ 20 ]. The increased amount of polyphenols in sample 11 z is also due to the addition of millet flour, made by grinding millet.…”
Section: Resultssupporting
confidence: 93%
“…From the obtained data it can be concluded that grape flour had a significant effect on the antioxidant activity and the amount of polyphenols. This fact is in accordance with an experiment from 2021, examining the effect of the addition of grape flour in concentrations of 1%, 3%, 5% and 10% on the antioxidant activity and total polyphenols [ 20 ]. The most acceptable samples were with 10% addition of flour.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Consequently, producers have been forced to design innovative products that meet customers' expectations, especially snacks such as cookies and sweets. This type of food is particularly desirable due to its easy availability and is a good basis for designing new products classified as a functional food, which is perceived as a healthier replacement for traditional foodstuffs [11,12]. Enrichment is one of the methods for functional food production.…”
Section: Introductionmentioning
confidence: 99%
“…Enrichment is one of the methods for functional food production. The composition of snacks can be improved using various ingredients (e.g., vitamins, microelements, fiber, or antioxidant substances) contained in numerous species of plants [11]. Bakery products are a good food matrix to obtain products with increased bioactive properties as they are popular with consumers and constitute the main part of their daily diet [13].…”
Section: Introductionmentioning
confidence: 99%